Attitude of junior schoolchildren and parents to the recommended volume of weekly motor activity - Evseev S.P. ,; Nenakhov I.G. ,; Shelekhov A.A. ,; Aksenov A.V. , (Theory and Practice of Physical Culture, 2024)
Objective of the study was to analysis of the attitude of primary school children and their parents to the recommended volumes of weekly physical activity. Methods and structure of the study. A survey was conducted of 309 school-age children studying in 10 schools in St. Petersburg and the Leningrad region. Of these, 143 respondents were children of primary school age (6-9 years old). Results and conclusions. It was revealed that a significant proportion of children of primary school age and their parents tend to believe that the amount of physical activity in the range of 180-360 minutes per week is sufficient for schoolchildren in this group. This range combines the necessary amount of physical activity to prevent the onset of symptoms of physical inactivity, ensure the process of physical development, and also save time for free leisure. A group of children whose volume of physical activity exceeds 360 minutes per week is considered insufficient. Parents of this group of children, whose volume of physical activity exceeds 360 minutes per week, and in exceptional cases reaches 900 and 1020 minutes per week, also tend to consider it insufficient. Thus, the question of the upper limit of the volume of physical activity of school-age children, both daily and weekly, remains relevant for study. It is necessary to establish a threshold that has sufficient developmental potential, ensures an improvement in the health of children and contributes to their harmonious development.